2016
DOI: 10.1155/2016/4647830
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicological Effects of an Aqueous Extract of Shells from the Pecan Nut Carya illinoinensis (Wangenh.) K. Koch and the Possible Association with Its Inorganic Constituents and Major Phenolic Compounds

Abstract: Background. Industrial processing of the pecan nut Carya illinoinensis K. Koch generated a large amount of shells, which have been used to prepare nutritional supplements and medicinal products; however, the safe use of shells requires assessment. This study evaluated the toxic, genotoxic, and mutagenic effects of pecan shell aqueous extract (PSAE) and the possible contribution of phenolic compounds, ellagic and gallic acids, and inorganic elements present in PSAE to induce toxicity. Results. Levels of inorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In subacute studies, Porto et al (2013) determined that no toxic effect was observed on Wistar rats summited to doses of 100 mg/kg for 28 days, a doses that showed some beneficial effects, such as decrease in TAG and body weight. The same group (Porto et al, 2015b) observed no toxic effect of doses up to 200 mg/kg for 3 days in CF-1 mice. Authors concluded that when using nutshell extracts the high levels of inorganic elements should be considered for safety reasons.…”
Section: Biological Activity Of Pecan By-productsmentioning
confidence: 81%
See 1 more Smart Citation
“…In subacute studies, Porto et al (2013) determined that no toxic effect was observed on Wistar rats summited to doses of 100 mg/kg for 28 days, a doses that showed some beneficial effects, such as decrease in TAG and body weight. The same group (Porto et al, 2015b) observed no toxic effect of doses up to 200 mg/kg for 3 days in CF-1 mice. Authors concluded that when using nutshell extracts the high levels of inorganic elements should be considered for safety reasons.…”
Section: Biological Activity Of Pecan By-productsmentioning
confidence: 81%
“…Gad et al (2007)determined an LD50 of 8.3 g/kg for an ethanolic leave extract in Sprague Dawley rats. Porto et al (2015b) determined the acute LD50 of aqueous nutshell extracts to be higher than 2 g/ kg for Wistar rats and 1166 mg/kg for CF-1 mice. Hawary et al…”
Section: Biological Activity Of Pecan By-productsmentioning
confidence: 99%
“…In this context, studies have shown that aqueous extracts of pecan shells (rich in acids such as gallic, 4-hydroxybenzoic, vanillic, chlorogenic, caelic and ellagic) have the ability to induce breast cancer cell death and increase breast cancer survival time of patients with certain tumors [18,27]. Also, shell in fresh condition has been used in nutraceutical products against obesity, hypercholesterolemia and as a source for the precaution of metabolic and inflammatory diseases, neurological disorders, gastric ulcers, and cancer [28]. These residues act as antinociceptive and antiedematogenic materials due to the high concentration of rutin, or vitamin P, in its composition [29].…”
Section: Disease Preventionmentioning
confidence: 99%
“…A study by Hilbig and co-workers (2018) have shown that pecan nut shell extracts effectively reduced viability of the breast cancer tumor cells and intensi ed cell death. Another study by Porto et al (2016) reported that pecan shell extracts did not induce DNA damage or mutagenicity.…”
Section: Introductionmentioning
confidence: 98%